Pengaruh Customer Experience , Brand Trust, terhadap Repurchase Intention melalui Customer Satisfaction sebagai Variabel Intervening (Studi pada Konsumen Suzuki Pick Up di Kota Cilacap) - Muhammad Dhiaulhaq Shidqi; Naili Farida; Robetmi Jumpakita Pinem (Universitas Diponegoro, 2022)
Suzuki Carry Pick Up as a commercial car that helps business in distributing goods. It is suspected that experience, trust, and satisfaction are factors that influence the interest in repurchasing Carry Pick Up. Background of this reseach is sales data from 2016 to 2020 experiencing fluctuating sales at Carry Pick Up in the city of Cilacap. The purpose of the study was to analyze the relationship between variables on Carry Pick users in Cilacap City using the type of explanatory research by taking 100 samples using nonprobability sampling, purposive sampling. Data were collected through a questionnaire. To test the validity, reliability test, correlation coefficient, multiple linear regression, coefficient of determination, t-test, and Sobel using the Spss version 26 and Sobel Test with quantpsy.org. The results showed that the positive influence between Customer Experience on Customer Satisfaction, a positive influence between Brand Trust on Customer Satisfaction, Customer Satisfaction on Repurchase Intention, Customer Experience on Repurchase Intention, Brand Trust on Repurchase Intention, Customer Experience on Repurchase Intention through Customer Satisfaction, and Brand Trust on Repurchase Intention through Customer Satisfaction. The recommendations from Suzuki Carry Pick Up able to improve product quality, and provide the best service. Suzuki Carry Pick Up sebagai mobil niaga yang membantu para pelaku usaha dalam pendistribusian barang. Diduga pengalaman, kepercayaan, dan kepuasan menjadi faktor yang berpengaruh terhadap minat pembelian kembali Carry Pick Up. Penelitian ini dilatarbelakangi data penjualan tahun 2016 hingga tahun 2020 mengalami penjualan yang fluktuatif pada Carry Pick Up di kota Cilacap. Tujuan penelitian untuk menganalisis hubungan antar variabel pada pengguna Carry Pick di Kota Cilacap dengan menggunakan tipe penelitian eksplanatory Research dengan mengambil sampel sebanyak 100 menggunakan teknik nonprobability sampling, purposive sampling. Data dikumpulkan melalui angket kuesioner. Untuk uji validitas, uji reliabilitas, koefisien korelasi, regresi linier berganda, koefisien determinasi, uji signifikansi (uji t), dan uji sobel menggunakan Spss versi ke 26 dan Sobel Test dengan quantpsy.org. Hasil penelitian menyatakan ada pengaruh yang positif antara Customer Experience terhadap Customer Satisfaction, pengaruh positif antara Brand Trust terhadap Customer Satisfaction, Customer Satisfaction terhadap Repurchase Intention, Customer Experience terhadap Repurchase Intention, Brand Trust terhadap Repurchase Intention, Customer Experience terhadap Repurchase Intention melalui Customer Satisfaction, dan Brand Trust terhadap Repurchase Intention melalui Customer Satisfaction. Adapun saran dari peneliti kepada Suzuki Carry Pick Up mampu meningkatkan kualitas produk, dan memberikan pelayanan yang terbaik.